1992
DOI: 10.1111/j.1432-1033.1992.tb17308.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin‐like‐growth‐factor‐II gene expression in rat liver cells

Abstract: The rat insulin-like-growth-factor-(1GF)-I1 gene is expressed at high levels during embryonic and fetal life and at low levels in adult animals. To study the regulation of IGF-I1 gene expression, we analyzed the synthesis and localization of the IGF-I1 transcripts in cultured rat liver cells either expressing (BRL3A cells) or not expressing (BRL30E and F A 0 cells) the IGF-I1 mRNA. The IGF-I1 gene is transcribed at a similar rate in expressing and non-expressing cells, whereas its nuclear and cytoplasmic RNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…When studying EGF receptor RNA in A431 epidermoid carcinoma cells, exon sequences were localized to two sites around the nucleolus, only one of which overlapped the intron sequences (Sibon et al, 1996). There also may be an increased destabilization and degradation of cytoplasmic mRNA (Zarrilli et al, 1992;Sachs, 1993;Beelman and Parker, 1995). Whether mature SNAP-25a protein is formed is not clear, although high levels of mature EGF receptor protein have been found in A431 cells expressing nuclear EGF receptor RNA transcripts (Wrann and Fox, 1979;Sibon et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…When studying EGF receptor RNA in A431 epidermoid carcinoma cells, exon sequences were localized to two sites around the nucleolus, only one of which overlapped the intron sequences (Sibon et al, 1996). There also may be an increased destabilization and degradation of cytoplasmic mRNA (Zarrilli et al, 1992;Sachs, 1993;Beelman and Parker, 1995). Whether mature SNAP-25a protein is formed is not clear, although high levels of mature EGF receptor protein have been found in A431 cells expressing nuclear EGF receptor RNA transcripts (Wrann and Fox, 1979;Sibon et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…1). We observed a synergistic effect rather than additive effect on DNA fragmentation with the combination of Ang II (10 −8 M) and IGF-IR antibody (20,40, and 60 ng/ml) Fig. 4 (a) The IGF-II and IGF-IIR protein products were induced by antisense IGF-I, IGF-IR antibody or IGF-I antibody.…”
Section: Apoptosis Measured By Dna Fragmentation Was Induced By Ang Imentioning
confidence: 91%
“…DNA ladder formation revealed that cardiac H9c2 cell underwent DNA fragmentation when exposed to either Ang II (10 −8 M) or IGF-IR antibody (20,40, and 60 ng/ml), compared to the negative and positive controls (Fig. 1).…”
Section: Apoptosis Measured By Dna Fragmentation Was Induced By Ang Imentioning
confidence: 95%
See 1 more Smart Citation
“…The human and mouse IGF-II genes are also subject to genomic imprinting (12,26,31). In addition, regulation takes place at the levels of translation (25) and mRNA stability (21,27,48).…”
mentioning
confidence: 99%